2015
DOI: 10.1080/19393210.2015.1063014
|View full text |Cite
|
Sign up to set email alerts
|

Aflatoxin B1and aflatoxins in ground red chilli pepper after drying

Abstract: In this study, 180 red chilli pepper (RCP) berry samples were obtained from two different croplands of Gaziantep and Kahramanmaraş (Turkey) in August, September and October. RCP berry samples were dried under sunlight and grinded. Ground red chilli pepper (GRCP) samples were analysed for aflatoxins (AFs, sum of B1, B2, G1 and G2) and AFB1 contamination. According to the results, in 49 of 180 samples, AFB1 and in 37 samples, AFs were higher than legal limits. The lowest amounts of AFs and AFB1 were obtained in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 27 publications
1
11
0
Order By: Relevance
“…The Nabeul governorate is a major agricultural region in Tunisia with large segments of irrigated cultures dedicated to the production of oranges (Citrus reticulata) or chili pepper (Capsicum), the latter used in the national condiment Harissa. The spoilage of oranges (i.e., fruits and juice) or chili pepper with Aspergillus and their subsequent contamination by aflatoxin have been already described (35,36). Our results should represent a strong incentive to conduct field studies in Nabeul governorate and elsewhere in the country with the aim of finding the eventual source of AFB1.…”
Section: Recent Work Have Shown That -124c>t Mutation Insupporting
confidence: 62%
“…The Nabeul governorate is a major agricultural region in Tunisia with large segments of irrigated cultures dedicated to the production of oranges (Citrus reticulata) or chili pepper (Capsicum), the latter used in the national condiment Harissa. The spoilage of oranges (i.e., fruits and juice) or chili pepper with Aspergillus and their subsequent contamination by aflatoxin have been already described (35,36). Our results should represent a strong incentive to conduct field studies in Nabeul governorate and elsewhere in the country with the aim of finding the eventual source of AFB1.…”
Section: Recent Work Have Shown That -124c>t Mutation Insupporting
confidence: 62%
“…Frequent contamination of Aflatoxin in spices in tropical countries is attributed to atmospheric temperature, humidity and the drying and processing conditions. Several countries reported contamination of aflatoxin in ground red pepper [12][13][14]. Several other spices such as cumin, black pepper, cardamom, ginger, coriander etc.…”
Section: Spicesmentioning
confidence: 99%
“…For instance, In Turkey, Ozkan etal. 28 analyzed 180 samples of red chili for AFs and AFB1. They found that total AFs and AFB1 in 20.5% and 27.5 % of samples was higher than the legal limits of Turkish food codex.…”
Section: Resultsmentioning
confidence: 99%